2005
DOI: 10.1097/01.mlr.0000163641.86870.af
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Medication Adherence on Hospitalization Risk and Healthcare Cost

Abstract: For some chronic conditions, increased drug utilization can provide a net economic return when it is driven by improved adherence with guidelines-based therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
1,078
3
32

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,467 publications
(1,137 citation statements)
references
References 31 publications
24
1,078
3
32
Order By: Relevance
“…The degree to which patients adhere to medication also has larger societal ramifications. One large retrospective study found that high rates of medication adherence were associated with lower disease-related medical costs and significantly lower hospitalization rates for patients with diabetes, hypertension, hypercholesterolemia, and congestive heart failure [10]. Similar relationships were observed when adherence and health care costs were analyzed in patients with HIV [11] and osteoporosis [12].…”
Section: Introductionmentioning
confidence: 74%
“…The degree to which patients adhere to medication also has larger societal ramifications. One large retrospective study found that high rates of medication adherence were associated with lower disease-related medical costs and significantly lower hospitalization rates for patients with diabetes, hypertension, hypercholesterolemia, and congestive heart failure [10]. Similar relationships were observed when adherence and health care costs were analyzed in patients with HIV [11] and osteoporosis [12].…”
Section: Introductionmentioning
confidence: 74%
“…Despite the benefit of antihypertensive therapies, many studies suggested suboptimal adherence to these medications, particularly among older adults with multiple chronic conditions 4, 5, 6, 7, 8, 9, 10, 11. Nonadherence to antihypertensives is associated with increased risk for CVD, hospitalization, and healthcare costs 5, 12, 13, 14, 15, 16, 17. Many observational studies examined the relationship between antihypertensive adherence and CVD outcomes in the general hypertension population 5, 13, 17.…”
Section: Introductionmentioning
confidence: 99%
“…Although effective pharmaceutical treatments are readily available and reduce the risk for major cardiovascular diseases,4 inadequate adherence among patients to hypertension medication and the inertia of physicians to intensify treatment contribute to substantial morbidity, mortality, hospitalization, and health care costs 5, 6, 7. Recent studies suggest that treatment intensification improves hypertension management even with suboptimal adherence and reduces risks of cardiovascular events and deaths 8, 9, 10, 11.…”
Section: Introductionmentioning
confidence: 99%